Multi dimensional system for evaluating preventive program for upper extremity disorders among computer operators. - Soares, Marcelo M.; Jacobs, Karen; Levanon, Yafa; Gefen, Amit; Lerman, Yehuda; Givon, Uri; Ratzon, Navah Z. (Work)
Typing is associated with musculoskeletal complaints (MSCs), caused by multiple risk factors. Although a wide variety of ergonomic intervention programs were conducted to reduce risk factors and MSC's, only few of them were found evidence based. This study aimed to test the efficacy of a workplace intervention in reducing MSC's among computer workers. 66 computer workers were assigned randomly to one of three intervention programs: ergonomic intervention including biofeedback, intervention without biofeedback and control group without intervention. The efficacy was tested by advanced assessment including; pain location and severity, posture at work, upper extremity 3D kinematics, muscle activity and psychosocial status. Working hypothesis; significant score differences will be found between the study groups which underwent ergonomic intervention and the control group on the following measures: pain complaints, upper extremity kinematics, muscle activity and psychosocial status. Significant differences were found between pre and post intervention and between research groups and the control group in pain, posture and motion. The ergonomic intervention with biofeedback had no unique contribution in comparison to other interventions. In conclusion; the proposed intervention program was found efficient for reducing pain among computer workers.